Elemen Pariwisata Berkelanjutan di Desa Sade - Agustiani, Indah Nur; Tiani, Maya Sulis; Maulana, Anggi; Ismi, Fayza Tiara; Pramesti, Fadillah Ayska; Rabbani, Jelita; Hidayat, Widiya Hidayanti; Aria, Maulana Zhahir (Manajemen dan Pariwisata, 2025)
Sade Village, located in Lombok, is a cultural tourism village that maintains the traditions of the Sasak people. Along with the development of tourism, the challenges in maintaining the sustainability of the environment, culture and also the welfare of local communities are increasing. This research aims to identify and analyze the elements of sustainable tourism implemented in Sade Village. The methods used in this research include several methods as follows: field observations, interviews with local residents, and literature reviews related to sustainable tourism. The research results show that elements of sustainable tourism in Sade Village include preserving traditional culture, sustainable environmental management, and active involvement of local communities in tourism activities. Despite this, challenges such as pressure from ever-increasing tourist numbers and the risks of cultural commercialization still need to be addressed to ensure long-term sustainability. This research concludes that the implementation of sustainable tourism in Sade Village needs to be improved through policies that support cultural and environmental preservation, as well as increasing the capacity of local communities in dealing with changes caused by tourism.